Groundwater Studies for Sustaining Peatlands against Fire Disasters and Supporting Water Resources: 10.32526/ennrj/23/20250002 - Andrio, David; Islami, Nur; Darmayanti, Lita (Environment and Natural Resources Journal, 2025)
There are two main issues related to water resources in coastal areas covered by peat soil. The first problem is peat fires, which occur during the dry season and are difficult to extinguish because the characteristics of peat make it very flammable. The second problem is a lack of clean water resources for the needs of the surrounding community. This study investigates the feasibility of groundwater potential for prevention of peat fire tragedies, and groundwater resources for community use. This study employed an integrated approach that combined geoelectrical resistivity surveys with physical and chemical analyses of soil and groundwater to assess groundwater potential both as a water resource and as a preventive measure against peatland fires. The results of this study indicated that all groundwater samples were contaminated with seawater and exceeded the permissible limits set by the World Health Organization (WHO), making them unsuitable for human consumption. Except for the central and eastern parts of the study area, peat soil exhibited resistivity values ranging from 30 to 210 Ω·m, largely influenced by its fluid and clay content. Through interpretation of resistivity data, variations in sand and gravel content at different depths were identified. Shallow aquifers were present at a depth of 10 meters in the south and 12 meters in the north, and the peat soil had a thickness that varied up to 4 meters. Thus while the groundwater reserves in the study area are not fit for community use or consumption, they do appear sufficient to significantly reduce the risk of widespread peat fire disasters.